The interface of real world, lexicalization and conceptualization on the example of the Contact Sense of the German preposition an (on, at) and its Polish Spanish and English counterparts - Jolanta Mazurkiewicz-Sokołowska (Research in Language)
The paper takes up the issue of creating meanings, focusing the dynamic relation between lexicalization and conceptualization on the example of prepositions. By providing a systematic view of the specific meanings of the Contact Sense of the German preposition an (on, at) and its Polish, Spanish and English counterparts, the interface between the given real spatial relation of two objects, its lexicalization and the emerging conceptualization is highlighted. Special attention is paid to the role of the particular pieces of knowledge and experience being activated in creating these meanings in order to look closely at the concept of context as this context is usually interpreted differently by different researchers. The attempt to show what happens step by step when conceptualizing a real spatial relation and its linguistic expression fixed in the lexicalization pattern is motivated by the finding that the difficulty with clear determination and separation of the context information from the information actually creating the meaning is one of the reasons why studies on the cognitive aspects of the semantics of prepositions have been abandoned over time. The paper aims to contribute to the elaboration of an authoritative method of establishing and identifying meanings of prepositions, and to contribute to the discussion about the language-thought relation providing arguments supporting the view of language as a trigger for conceptualizations provided by the embodied cognition rather than as a tool shaping thoughts.